A pluma mantélica dos Açores e a sua importância para a composição em gases nobres (He e Ne) das lavas da ilha Terceira - Madureira, Pedro (2011)
The noble gases signature of Terceira lavas was recently described in terms of binary mixing between a MORB magma type and a plume component. The relative proportions estimated for these components show the strong predominance of MORB. This can be interpreted as a consequence from the localization of Terceira Island or, alternatively, can be explained by the last phases of plume activity as imaged by tomographic data.